Creation of a new version of the Constitution of the Republic of Uzbekistan and that it is important - Turgunov Muhammad Babur (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article at the history of the creation of our Constitution, the importance of him in its application to the lives of citizens, the protection of the rights and freedoms of each citizen by law and the equality of the law for all are covered.